Is rotavirus diarrhea a systemic viral infection? - (:unkn) unknown (My University, 2010)
Objective: To evaluate the development of extraintestinal complications related to rotavirus gastroenteritis, and to determine the impact of systemic rotavirus on disease burden in children with rotavirus-induced diarrhea in our hospital. Methods: During the two-year study period, 353 children with confirmed rotavirus gastroenteritis were recruited. Results: Extraintestinal complications occurred in 9.6% (34/353) of all the children. Fourteen patients had central nervous system (CNS) complications related to rotavirus infection. Among these 14 patients, 6 patients had encephalitis; 6 patients, febrile seizures, and 2 patients, aseptic meningitis. Frequency of neutropenia was 2.54% in the study population. Six patients had severe neutropenia [absolute neutrophil count (ANC) <500], and three patients had mild neutropenia [ANC>500]. Ten patients had secondary bacteremia after rotavirus gastroenteritis. Incidence of bacteremia was 2.83%. One patient had myocarditis, which was thought to be associated with rotavirus infection. One death (a child with metabolic disorder) occurred during 2 years. Conclusion: Our results support the plausibility of rotavirus as an etiologic factor for the clinical manifestations associated with rotavirus infection and highlight the need to pursue studies to determine the involvement of rotavirus as a cause of non-gastrointestinal diseases. The impact of systemic rotavirus on disease burden remains to be determined.
Keywords: Complication; Extraintestinal; Rotavirus; Systemic; Viremia